Factors Negatively Influencing Postoperative Improvement After Laminoplasty in Degenerative Cervical Myelopathy. Issue 1 (February 2022) - Inose, Hiroyuki; Yoshii, Toshitaka; Kimura, Atsushi; Takeshita, Katsushi; Inoue, Hirokazu; Maekawa, Asato; Endo, Kenji; Furuya, Takeo; Nakamura, Akira; Mori, Kanji; Kanbara, Shunsuke; Imagama, Shiro; et al.
Abstract : Study Design: This was a retrospective study of prospectively collected data. Objective: In this study, we aimed to characterize a population of patients with degenerative cervical myelopathy (DCM) and a history of poor postoperative neurological recovery and to identify risk factors associated with poor neurological recovery after laminoplasty. Summary of Background Data: Kyphotic cervical alignment has been considered a relative contraindication to laminoplasty in recent years; hence, laminoplasty has been decreasingly performed for the treatment of DCM in patients with cervical kyphosis. However, the effect of global spinal alignment on postoperative outcomes has not been extensively investigated. Materials and Methods: We prospectively enrolled patients who were scheduled for laminoplasty for DCM. Outcome (at enrollment and 1 y after surgery) and risk factor analyses were performed by comparing the good recovery and poor recovery groups. The Spearman correlation coefficient was used to evaluate the relationships between the recovery rate and the preoperative radiographic factors. Results: In total, 101 patients completed the 1-year follow-up. Regarding clinical outcomes, the Japanese Orthopedic Association score for the assessment of cervical myelopathy, European Quality of Life-5 Dimensions, and Neck Disability Index scores improved postoperatively. The recovery rate was significantly correlated with the preoperative sagittal vertical axis (SVA). The patients in the poor recovery group were older than those in the good recovery group. Univariate analyses showed that the SVA and T1 pelvic angle were significantly higher in the poor recovery group. Lastly, stepwise logistic regression analysis showed that a higher SVA was an independent predictor of poor recovery after laminoplasty. Conclusions: The SVA and T1 pelvic angle were significantly higher in the poor recovery group. A high preoperative SVA is an independent predictor for poor recovery after laminoplasty. Therefore, indications for laminoplasty in elderly DCM patients with a high preoperative SVA should be carefully considered. Level of Evidence: Level III.